Wireless Technologies for Internet of Things - กอเจริญ, รศ.ดร. ปรีชา (Journal of Digital Communications, 2017)
Communication is a key factor of the Internet of Things (IoT). Variety of technologies and standards of communication protocol have been used in IoT. Connecting IoT devices need networking to pass information between devices in different networks. There are pros and cons. for each technology that were introduced. Choosing the technology or standard that suit to the application, it is necessary to have a basic understanding of the technology and their limitations. This article presents the fundamentals of wireless communication technology for IoT, the limits of the technology, and the recommendation.